Study on the Change Law of Red-Green-Blue Values of Infrared Thermal Image in the Process of Anthracite Oxidation and Spontaneous Combustion - Wang, Liancong; Hu, Weizhao; Hu, Yuan (Frontiers in Materials, 2022)
As the coal with the highest degree of coalification, anthracite is usually regarded as a mixture composed of organic and inorganic substances, with the characteristics of polymers and composites. It is very important to study the oxidation and spontaneous combustion characteristics of anthracite for the thermal properties of coal-based polymers and composites. Anthracite exhibits varying oxidation and spontaneous combustion characteristics at various stages of the oxidation and spontaneous combustion process, which cannot be fully demonstrated by the coal temperature alone. As a result, this paper develops an online method for characterizing the RGB values of infrared thermal images. The variation of the RGB value of an infrared thermal image during the oxidation and spontaneous combustion of anthracite was investigated. The findings show that there is a clear relationship between R (red), G (green), B (blue), RGB (red/green/blue) values, and coal temperature during the oxidation and spontaneous combustion of anthracite. The R and the G value curves each have one characteristic peak and two characteristic valleys in the experiment. However, the overall change range of the G value curve is relatively small; the B value curve has two characteristic peaks and one characteristic valley. There are no characteristic peaks and valleys in the RGB value curve, despite the influence of experimental instruments and the experimental environment.